Priscillianism Today: Balance, Perspectives and Contributions on Imperial Interference in Ecclesiastical Conflicts - Escribano Paño, Mª Victoria (Gerión. Revista de Historia Antigua, 2021)
This paper provides a critical and selective analysis of the most recent contributions to studies on Priscillianism. This study also presents a renewed interpretation of the intervention of Magnus Maximus in the trials at Trier. The letters Magnus Maximus sent to Valentinian II and Siricius consist of diplomatic texts which meet a specific function befitting his political strategy in 386. In both letters, written almost in unison in 386, Maximus strived to justify his part in the trials of Trier, implicitly before Valentinian and explicitly before Siricius, using the arguments he had heard from Martin of Tours and Ambrose: the emperor ought not to intervene directly in heretical disputes; he should delegate to the bishops, who were to resolve the internal conflicts amongst churches.
Keywords: Heresy; Magnus Maximus; Valentinian II; Ambrose; Siricius